COMPETENCE DEVELOPMENT IN PROFESSIONAL NURSING CARING BEHAVIORS AMONG NURSING STUDENTS DURING ACADEMIC AND PROFESSIONAL PROGRAMS IN THREE NURSING EDUCATIONAL INSTITUTIONS IN THREE PROVINCES IN INDONESIA - Yulia, Yulia; Okti, Purwanti; Nelwati, Nelwati; Ernawati, Ernawati; Krisna, Yetty; Wendy, Abigail (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2024)
Introduction: Professional nursing caring behaviors can be learned through education. Indonesian research on this area remains limited. This study explores the development of nursing students' professional caring behaviors and clinical learning processes that support them. Method:This ethnographic study involved 34 observations of nursing student clinical practices, field notes, and six focus group discussions with students and clinical instructors from three nursing education institutions across three provinces. Data analysis was conducted using qualitative content analysis. Result: Ten themes revealed: professional nursing caring behaviors are understood as altruistic behaviours, holistic, therapeutic, and bureaucratic dimensions; instrumental caring predominates in student clinical practices; physical interventions serve as the entry point for communication; the provision of information is dominant in interpersonal communication; cultural sensitivity and touching are expressions of caring behaviors; clinical role models, knowledge, and experience are vital in developing professional caring behaviors; patient negative responses, clinical workload, and patient complexity pose challenges in developing professional nursing caring behaviors; insufficient clinical mentoring impacts the achievement of competencies; students' lack of self-confidence is perceived as 'uncaring' behaviors; and there is insufficient collaboration to ensure the attainment of non-instrumental caring competencies. Conclusion: Students' competencies in professional caring behaviors evolve during their educational journey, though the focus remains on instrumental caring. Knowledge, clinical exposure, experiences, role models, and self-confidence are crucial in enhancing professional nursing caring competencies. Clinical learning guidelines, such as preceptorship and collaborative learning models in professional nursing caring competencies, should be considered to develop the skills.